(untitled) (Andamios, Revista de Investigación Social, 2011)
Heritage tourism has flourished in the last three decades. Its importance has prompted the emergence of different kinds of analysis that have consolidated the heritage tourism as a topic in the academic debate. The present paper shows an anomalous case of heritage tourism: the ‘ex haciendas’ in the Xalapa area. The discussion of this case allows us to rethink and reopen the implicit assumptions of this topic. In doing so, we can present alternative ways as the old ‘haciendas’ are being visited and experienced as tourist sites.